Clinical features and prognostic factors for liver cancer from a referral center in northern Thailand - Apinya Leerapun (2018)
Background: Primary liver cancer, included hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA), is the leading cancer with high mortality in Thailand. We aim to evaluate the overall survival and predictor of mortality in patients with HCC and CCA. Material and Method: We reviewed medical records of 786 patients with liver mass between July 2007 and June 2010, 287 patients were HCC and 449 patients were CCA. The overall survival and prognostic variables for survival were analyzed. Results: The mean age of HCC patients and CCA patient were 53.8 years and 59.2 years. Male was predominant, 85% and 74% in HCC and CCA. By BCLC staging for HCC, patients at early stage (A), intermediate stage (B), advanced stage (C), and terminal stage (D) were 40 (13.9%), 105 (36.6%), 95 (33.1%), and 43 (15.0%). Among 449 CCA patients, 143 (31.8%) were intrahepatic type and 306 (68.2%) were ductal type. The mean follow-up time for HCC and CCA patients were 20.1 and 16.7 months. The 1-year, 2-year, and 3-year survival of HCC and CCA were 55%, 34%, 31.3% and 54%, 21.2%, 19.1%, respectively. Predictor of death in HCC patients included portal vein thrombosis and did not receive any treatment (p < 0.05). Meanwhile, the predictor of death in CCA patient included intrahepatic type, total bilirubin > 2 mg/dl, CA 19-9 > 100, and unresectable tumor (p < 0.05). Conclusion: The survival of patients who received any type of treatment was much better than in the past. Still, in patients with advanced disease whom only supportive treatments were provided, the prognosis is grave.